A new and cryptic species of Trentepohlia (Ulvophyceae, Chlorophyta) from Brazilian mixed forests - Lemes-Da-Silva, Nadia M. [UNESP]; López-Bautista, Juan M.; Branco, Luis Henrique Z. [UNESP] (Taylor & Francis, 2018)
The order Trentepohliales represents one of the most prominent algal groups in terrestrial habitats but its taxonomy and phylogeny are still poorly understood. During a survey of Trentepohliales in different Brazilian biomes, some trentepohlialean populations were found in mixed forest localities growing on the bark of the gymnosperm Araucaria angustifolia. These populations formed orange patches with the typical habit of the genus Trentepohlia. The filaments consisted of cylindrical or swollen cells 4.0–10.2 lm wide and produced single apical globular gametangia and zoosporangia, with apical cells having a well-developed pectic cap. Molecular analysis based on the rbcL gene revealed that these populations represent a distinct clade, and based on the results, a new species, Trentepohlia araucariana, is described.
Keywords: Chlorophyta; Morphology; RbcL rRNA gene; Terrestrial alga; Trentepohliales